2011
DOI: 10.1111/j.1478-4408.2011.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

Lighting in offices: lamp spectrum and brightness

Abstract: In UK offices, a ubiquitous target for lighting ‘design’ is an illuminance of 500 lux on the working plane. This article questions the basis for the 500 lux standard and suggests that a reduced illuminance would not affect visual performance. However, lighting design should also consider expectations and if a reduced illuminance leads to perceived gloom then this could affect motivation to carry out work tasks. Evidence is presented which suggests that the brightness of a space may be maintained, despite a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 70 publications
0
9
0
1
Order By: Relevance
“…Second, for the lighting designer, lamp choice offers the opportunity to increase the brightness of a space and/or to reduce the energy consumed by the lighting. 67 Knowledge of the spectral response of human vision is of practical significance because light sources developed for commercial use are usually developed to meet human visual needs: if photometry built solely on V() fails to faithfully characterise the brightness response to lit spaces, then light sources optimised for high luminous efficacy consistent with V() should not be expected to yield the highest brightness per watt of optical radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Second, for the lighting designer, lamp choice offers the opportunity to increase the brightness of a space and/or to reduce the energy consumed by the lighting. 67 Knowledge of the spectral response of human vision is of practical significance because light sources developed for commercial use are usually developed to meet human visual needs: if photometry built solely on V() fails to faithfully characterise the brightness response to lit spaces, then light sources optimised for high luminous efficacy consistent with V() should not be expected to yield the highest brightness per watt of optical radiation.…”
Section: Introductionmentioning
confidence: 99%
“…However, users require lighting that does not limit visual performance, does not cause visual discomfort and meets expectations . Illuminance of 500 lux is an accepted standard, but it has been suggested that lower light levels may be possible without compromising the user experience . The effects of illuminance (300 lux or 500 lux) and colour temperature (4000 K or 6500 K) were measured in mock office rooms ; observers preferred the 500 lux and warmer (4000 K) lighting.…”
Section: Learning Productivity and Alertness In Indoor Spacesmentioning
confidence: 99%
“…Current concerns about sustainability may lead to a reduction in illuminance levels in office light; in the commercial sector, lighting accounts for up to 40% of energy costs in a typical UK office . However, users require lighting that does not limit visual performance, does not cause visual discomfort and meets expectations . Illuminance of 500 lux is an accepted standard, but it has been suggested that lower light levels may be possible without compromising the user experience .…”
Section: Learning Productivity and Alertness In Indoor Spacesmentioning
confidence: 99%
“…Fotios examined the reliability of experiments dealing with apparent brightness, and came to the conclusion that one has to be very careful in designing the experiment to ensure meaningful results. 38 A recent paper by Fotios 39 discusses the question of lamp spectrum and brightness for office lighting, but also concentrates on lamp spectra of different CCT.…”
Section: Introductionmentioning
confidence: 99%